Efficiency of Production Factors in the EU - Martina Novotná; Tomáš Volek (DETUROPE)
The aim of the article is to consider, on the basis of indicators of effectiveness of production factors, the development of particular member states of the EU in the period 1996-2015 and relations between them in connection with the real business cycle in the EU and different starting positions (groups according to GVA per worker). The hypothesis that the development of labour productivity in the established groups of countries and at the intervals of the real economic cycle differs statistically significantly was verified based on the ANOVA test. The analysis illustrated different development and reaction of indicators of productivity in the monitored groups of the EU countries to the cyclic development of economies. It has been confirmed that the states with worse starting conditions have greater growth intensity in productivity and the business cycle does not interfere with the efficiency of production factors to any real extent.